Medication use in athletes selected for doping control at the Sydney Olympics (2000) - Corrigan, B.; Kazlauskas, R. (Clinical Journal of Sport Medicine, 2003)
During the Olympic Games held in Sydney in September, 2000 Doping Control was undertaken as specified in the International Olympic Code. During this process information about the medications taken by athletes was collected as a routine and formed part of the paperwork associated with a urine test. In their Post Games Report the World Anti-Doping Agency (WADA) recommended that the information about medications be collated with a view to assessing their use by athletes.